Designing a Heutagogy Curriculum Template for the Second Level of High School - Ziba Nikmohammadi; Nahid shafiee; Alireza Araghieh (Iranian Journal of Educational Research)
Objective: The current research was conducted with the aim of designing a Heutagogy curriculum model for the second level of high school in Tehran. Methods: The method of this research is applied in terms of purpose and it was done in an exploratory way that in the qualitative part of the method of thematic analysis and research synthesis and the quantitative part was based on structural equation modeling, the method of data collection was done in a mixed method (quantitative and qualitative) and the research tools in the qualitative part were semi-structured interviews and questionnaires and in the quantitative part. The questionnaire resulted from the qualitative phase. In the qualitative section, the Lausche coefficient (CVR) was used to check the content and Cohen's kappa coefficient was used to check the reliability. In this section, to validate the designed model, experts in curriculum and educational psychology completed the relevant questionnaire. In the qualitative section, data analysis was carried out using thematic analysis and research synthesis based on basic themes, organizing themes, and comprehensive themes. The quantitative part was based on structural equation modeling. The statistical population of the quantitative part includes all the secondary school teachers of Tehran city, who were selected using Cohen's formula, with a sample size of 198 people. Results: At first, the fit of the models related to each of the elements was extracted and at the end, the overall fit of the model was confirmed. The research findings were based on the results of qualitative and quantitative analyzes of the eight elements of flexibility, purpose, educational technology, thinking, facilitation, learner, content and Evaluation for heutagogy curriculum was identified in the second year of high school. Each element had dimensions and components; the total number of identified dimensions was 28 dimensions. Conclusions: The findings predominantly corroborate the formulation of a heutagogy curriculum for the second level of secondary education.